Emerging drugs and drug targets against tuberculosis. (21st April 2017) - Lambert, Nzungize; Abdalla, Abualgasim Elgaili; Duan, Xiangke; Xie, Jianping
Abstract: Mycobacterium tuberculosis (M. tuberculosis), the causative agent of tuberculosis, uses various tactics to resist on antibiotics and evade host immunity. To control tuberculosis, antibiotics with novel mechanisms of action are urgently needed. Emerging new antibiotics and underlying novel drug targets are summarized in this paper.